2020
DOI: 10.1177/0091217420973489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pre- and post-hemodialysis PHQ-9 depression scores in patients with end-stage renal disease: A cross-sectional study

Abstract: Objectives An overlap between the somatic symptoms of depression and those of uremia seen in end-stage renal disease (ESRD) patients may affect the diagnosis of depression. This study aims to evaluate the effect of hemodialysis on the diagnosis of depression among patients on maintenance hemodialysis as dialysis diminishes the uremic symptoms, and to compare depression scores before and after dialysis. Methods This was a cross-sectional analytic study conducted from November 2018 through April 2019, in three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…The findings reveal a notable depression prevalence of 63% among HD patients in Hodeida city, as determined by the PHQ-9 scale. While this prevalence is lower than the prevalence reported in China (73.8%) 32 but higher than that reported in Jordan (48.5%), 13 where both studies utilized the same scale. Other smaller-scale studies in Saudi Arabia and Lebanon reported lower prevalence rates of 24.6% and 40.8%, respectively, using the Hospital Anxiety and Depression Scale.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The findings reveal a notable depression prevalence of 63% among HD patients in Hodeida city, as determined by the PHQ-9 scale. While this prevalence is lower than the prevalence reported in China (73.8%) 32 but higher than that reported in Jordan (48.5%), 13 where both studies utilized the same scale. Other smaller-scale studies in Saudi Arabia and Lebanon reported lower prevalence rates of 24.6% and 40.8%, respectively, using the Hospital Anxiety and Depression Scale.…”
Section: Discussioncontrasting
confidence: 64%
“…The severity of depression was categorized based on the total score as none (0–4), mild (5–9), moderate (10–14), moderately severe (15–19), and severe (20–27). 13 , 27 In this study, the cutoff score of PHQ-9 was set at a total score of 10 and higher to identify patients with moderate or severe depression because its sensitivity and specificity were best balanced at this cutoff point, as revealed in previous studies. 23 , 28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AlAwwa et al ( 34 ) demonstrate that hemodialysis may not be associated with a greater or lesser presence of depressive symptoms. However, by including only patients on hemodialysis, our study aimed to homogenize the population studied and, mainly, to identify the influence of depression on the functional capacity and quality of life of patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression in this population is well known (34,35). In a cross-sectional study, more than 66% of the evaluated patients had depressive disorders.…”
Section: Discussionmentioning
confidence: 99%